ALTERAÇÕES HISTOPATOLÓGICAS DA MUCOSA GÁSTRICA NO CURSO DA INFECÇÃO PELO Helicobacter pylori - Rodrigues, Obirajara; Mendonza-Amaral, Daoiz; Graudenz, Marcia Silveira; Sparvoli, Antônio Cardoso; Pires, José Fernando; Piano, Leonardo (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento